C10orf99/GPR15L Regulates Proinflammatory Response of Keratinocytes and Barrier Formation of the Skin - Dainichi, Teruki; Nakano, Yuri; Doi, Hiromi; Nakamizo, Satoshi; Nakajima, Saeko; Matsumoto, Reiko; Farkas, Thomas; Wong, Pui Mun; Narang, Vipin; Moreno Traspas, Ricardo; Kawakami, Eiryo; Guttman-Yassky, Emma; et al. (Frontiers in Immunology, 2022)
The epidermis, outermost layer of the skin, forms a barrier and is involved in innate and adaptive immunity in an organism. Keratinocytes participate in all these three protective processes. However, a regulator of keratinocyte protective responses against external dangers and stresses remains elusive. We found that upregulation of the orphan gene 2610528A11Rik was a common factor in the skin of mice with several types of inflammation. In the human epidermis, peptide expression of G protein-coupled receptor 15 ligand (GPR15L), encoded by the human ortholog C10orf99, was highly induced in the lesional skin of patients with atopic dermatitis or psoriasis. C10orf99 gene transfection into normal human epidermal keratinocytes (NHEKs) induced the expression of inflammatory mediators and reduced the expression of barrier-related genes. Gene ontology analyses showed its association with translation, mitogen-activated protein kinase (MAPK), mitochondria, and lipid metabolism. Treatment with GPR15L reduced the expression levels of filaggrin and loricrin in human keratinocyte 3D cultures. Instead, their expression levels in mouse primary cultured keratinocytes did not show significant differences between the wild-type and 2610528A11Rik deficient keratinocytes. Lipopolysaccharide-induced expression of Il1b and Il6 was less in 2610528A11Rik deficient mouse keratinocytes than in wild-type, and imiquimod-induced psoriatic dermatitis was blunted in 2610528A11Rik deficient mice. Furthermore, repetitive subcutaneous injection of GPR15L in mouse ears induced skin inflammation in a dose-dependent manner. These results suggest that C10orf99/GPR15L is a primary inducible regulator that reduces the barrier formation and induces the inflammatory response of keratinocytes.